Interplay Between Socioeconomic Status and Otitis Media Disease Burden in Resource-rich and Resource-poor Nations. Issue 9 (October 2018) - Guys, Nicholas; Ramsey, Tam; Kandinov, Aron; Svider, Peter F.; Jyung, Robert W.; Hong, Robert; Sheyn, Anthony
Abstract : Objectives/Hypothesis: To characterize global differences in otitis media (OM)-related disease burden between socioeconomically advantaged and disadvantaged nations. Methods: Using the Global Health Data Exchange, worldwide OM burden was evaluated using age-standardized disability-adjusted life years (DALYs) per 100, 000 individuals in 183 countries from 1990 to 2015. Countries were organized by socioeconomic status using Human Development Index (HDI) values collected from the United Nations Development Program. Gini coefficients and concentration indices were employed to analyze disparities in OM disease burden. Results: From 1990 to 2015, the mean DALY rate across all nations decreased by 21.9%. When considering disease burden in relation to socioeconomic status, age-standardized DALYs decreased as HDI values increased ( p  < 0.001). For both children and adults, DALY rates were significantly different between HDI groups ( p  < 0.01). Gini coefficients decreased from 0.821 in 1990 to 0.810 in 2015, indicating a modest reduction in international health inequality. Global disparities in OM disease burden, as measured by the concentration index, worsened from 1990 to 2010 before showing a small trend reversal in 2015. Conclusions: To our knowledge, this is the first analysis investigating socioeconomic-related global disparities in OM disease burden using HDI values, Gini coefficients, and concentration indices. While the overall mean decrease in DALY rate from 1990 to 2015 is encouraging, the net decrease in concentration index during this period suggests less-developed nations continue to shoulder a disproportionate burden. Greater resource allocation to resource-poor nations may be warranted, as disease burden negatively impacts these countries to a greater degree.